ORGANIZATIONAL CITIZENSHIP BEHAVIOR, GAYA KEPEMIMPINAN TRANSFORMASIONAL, DAN PROFESSIONAL COMMITMENT SEBAGAI PREDIKTOR KEPUASAN KERJA KARYAWAN - Wiranata, Ida Bagus Eka; Utama, I Wayan Mudiartha (E-Jurnal Manajemen; Vol 5 No 12 (2016), 2016)
Business competition, especially in the services sector, pushed the company or organization to optimize its resources. The purpose of this study wanted to know the effect of organizational citizenship behavior (OCB), transformational leadership and professional commitment to job satisfaction of employees in Tuban Terminal CV Karya. This  sample of 61 of the number of employees through proportionate random sampling method. Technical analysis is used multiple linear regression. It was found that organizational citizenship behavior (OCB), transformational leadership and professional commitment influence have positively and significantly on employee job satisfaction.
Keywords: organizational citizenship behavior, transformational leadership style, professional commitment, job satisfaction